2008
DOI: 10.1186/1477-7525-6-34
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life as reported by school children and their parents: a cross-sectional survey

Abstract: BackgroundComprehensive evidence exists regarding the discrepancy between children's reports and parents' by proxy reports on emotional and behavioural problems. However, little is yet known about factors influencing the extent to which child self- and parent by proxy reports differ in respect of child Quality of Life (QoL). The aim of the study was to investigate the degree of discrepancy between child and parent by proxy reports as measured by two different QoL instruments.MethodsA representative Norwegian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
177
7
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(207 citation statements)
references
References 31 publications
17
177
7
6
Order By: Relevance
“…For example, Huppert and colleagues [27] found that QoL scores in individuals in remission tended to be between those of healthy controls and individuals with current OCD, and to not differ significantly from either group. Moritz and colleagues [31] found significantly improved QoL in therapy responders relative to non-responders but that compromised QoL persisted in most patients over time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Huppert and colleagues [27] found that QoL scores in individuals in remission tended to be between those of healthy controls and individuals with current OCD, and to not differ significantly from either group. Moritz and colleagues [31] found significantly improved QoL in therapy responders relative to non-responders but that compromised QoL persisted in most patients over time.…”
Section: Discussionmentioning
confidence: 99%
“…Psychometric testing of the KINDL-R revealed good scale utilization and scale fit as well as moderate internal consistency [26]. A Norwegian normative study also confirmed satisfactory internal consistency and test-retest reliability [27].…”
Section: Quality Of Life (Qol)mentioning
confidence: 96%
See 3 more Smart Citations